CULTURAL FILTERING STRATEGIES IN TRANSFERRING MEANING FROM ENGLISH INTO INDONESIAN - Karimah, Ayesha Sofiah (Journal of Language and Literature, 2021)
This research is an annotated translation research. In this research the researcher  discusses the linguistic patterns in transferring meaning from English into Indonesian. Empirically speaking, it naturally happens, when a text from a foreign language is going to be meaningfully transferred into another language. It is due to the fact that the language system of the foreign text is different from the language system of the target text. In this research the researcher was trying to find out the difficulties that are encountered by the researcher as a translator when translating a text from English into Indonesian, specifically in the culture-specific items. The problems found by the researcher will then be analyzed and given acceptable reasons by the researcher/translator for their solution. A novel entitled The Way We Were is used as the data source, meanwhile the research data is word or words lexically unequivalent to the target text. The research method is introspective and retrospective. The theory used to analyze the research data is Chesterman’s theory, specifically cultural filtering which is under the pragmatic strategies. From the findings of the research, the researcher concludes that out of four categories of cultural filtering strategies, only two were used. Out of the 6 data which are analyzed in this research, there are 4 data that use naturalization strategy, and 2 data used adaptation strategy.